Collaborative requirements review tool (collaborev) to support requirements validation - Nazurin, Jamaludin; Ahmad Kamran, Alya Aqilah; Azlin, Nordin (IIUM Press, 2024)
Requirements review involves a team ofreviewers,who will go throughthe requirementsin an attempt to find any requirements issues. The checklist-based technique is the most typically adopted method during requirements reviews. Due to the inconsistency and inefficiency of manual requirements review procedures, requirement engineers often find it challenging to effectively and productively review requirements. By streamlining the process with automated processes, collaborative features, and clear traceability, the web-based solution increases productivity, accuracy, and transparency of review. This innovative solution solves the shortcomings of manual procedures, paving the way for more fruitful software development endeavours. The software project was planned and managed using the Model-View-Controller (MVC) architecture framework and adopted an iterative prototyping methodology. The implementation of the project is using Laravel framework by utilizing PHP,JavaScript, HTML, CSS, Bootstrap, and MySQL.